ARGUMENTASI SYEKH NAWAWI BIN UMAR AL-BANTANI TENTANG KEDUDUKAN PEREMPUAN DALAM KELUARGA: KAJIAN FIQH KESETARAAN - Widiyarti Widiyarti; Rohmah Maulidia (IJouGS: Indonesian Journal of Gender Studies, 2021)
Abstract: The behavior of human life can not be separated from its perspective on a concept or thought that it believes in. This study aims to explore thougts and arguments of Sheikh Nawawi and then analyze them in the framework of gender equality and Mubadalah relations in the life of husband and wife. Textually, behalf on Uqudullujain, explains that the position of woman is not equal to the man. The husband is allowed to beat his wife if the wife does not carry out the husband’s order, especially to make up and preen, refuse to be invited to sleep together, and the wife is also not allowed to ask for a divorce.Keyword: Gender, equality, womanAbstrak: Perilaku kehidupan manusia tidak dapat terlepas dari cara pandangnya terhadap sebuah konsep atau pemikiran yang diyakininya. Tulisan ini mengekplorasi pemikiran dan argumentasi Syekh Nawawi kemudian menganalisisnya dalam bingkai kesetaraan gender dan relasi mubadalah dalam kehidupan suami istri. Secara tekstual, kitab Uqudullijain menjelaskan kedudukan perempuan tidak setara dengan laki-laki. Suami diperkenankan memukul istri, jika istri tidak mengindahkan perintahnya untuk berhias dan bersolek, menolak diajak tidur bersama, serta istri juga tidak diperkenankan meminta cerai. KataKunci: Gender, kesetaraan, perempuan